Two ovarian candidate enhancers, identified by time series enhancer RNA analyses, harbor rare genetic variations identified in ovarian insufficiency. Issue 13 (3rd February 2022) - Nakagawa, Ryuichi; Takasawa, Kei; Gau, Maki; Tsuji-Hosokawa, Atsumi; Kawaji, Hideya; Murakawa, Yasuhiro; Takada, Shuji; Mikami, Masashi; Narumi, Satoshi; Fukami, Maki; Sreenivasan, Rajini; Maruyama, Tetsuo; et al.
Abstract: The genetic regulation of ovarian development remains largely unclear. Indeed, in most cases of impaired ovarian development—such as 46, XX disorders of sex development (DSD) without SRY, and premature ovarian insufficiency (POI)—the genetic causes have not been identified, and the vast majority of disease-associated sequence variants could lie within non-coding regulatory sequences. In this study, we aimed to identify enhancers of five ovarian genes known to play key roles in early ovarian development, basing our analysis on the expression of enhancer derived transcripts (eRNAs), which are considered to characterize active enhancers. Temporal expression profile changes in mouse WT1-positive ovarian cells were obtained from cap analysis of gene expression at E13.5, E16.5 and P0. We compared the chronological expression profiles of ovarian-specific eRNA with expression profiles for each of the ovarian-specific genes, yielding two candidate sequences for enhancers of Wnt4 and Rspo1. Both sequences are conserved between mouse and human, and we confirmed their enhancer activities using transient expression assays in murine granulosa cells. Furthermore, by sequencing the region in patients with impaired ovarian development in 24 patients, such as POI, gonadal dysgenesis and 46, XX DSD, we identified rare single nucleotide variants in both sequences. Our results demonstrate that combined analysis of the temporal expression profiles of eRNA and mRNA of target genes presents a powerful tool for locating cis -element enhancers, and a means of identifying disease-associated sequence variants that lie within non-coding regulatory sequences, thus advancing an important unmet need in forward human genetics.